2014
DOI: 10.1016/j.cub.2014.01.058
|View full text |Cite|
|
Sign up to set email alerts
|

Voice-Sensitive Regions in the Dog and Human Brain Are Revealed by Comparative fMRI

Abstract: During the approximately 18-32 thousand years of domestication, dogs and humans have shared a similar social environment. Dog and human vocalizations are thus familiar and relevant to both species, although they belong to evolutionarily distant taxa, as their lineages split approximately 90-100 million years ago. In this first comparative neuroimaging study of a nonprimate and a primate species, we made use of this special combination of shared environment and evolutionary distance. We presented dogs and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
181
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(201 citation statements)
references
References 47 publications
18
181
2
Order By: Relevance
“…Results revealed that dogs consistently turned their head to the right during presentation of human spoken commands with artificially increased segmental cues (i.e., higher salience of meaningful phonemic components); moreover, a significant left-turning bias was observed in response to manipulated commands with increased supra-segmental vocal cues (i.e., higher salience of intonation component). These results have been confirmed by recent neuroimaging studies and overall suggest a convergent lateralized brain specialisation between canine and human species for processing speech [9].…”
Section: Sensory Lateralizationsupporting
confidence: 76%
See 2 more Smart Citations
“…Results revealed that dogs consistently turned their head to the right during presentation of human spoken commands with artificially increased segmental cues (i.e., higher salience of meaningful phonemic components); moreover, a significant left-turning bias was observed in response to manipulated commands with increased supra-segmental vocal cues (i.e., higher salience of intonation component). These results have been confirmed by recent neuroimaging studies and overall suggest a convergent lateralized brain specialisation between canine and human species for processing speech [9].…”
Section: Sensory Lateralizationsupporting
confidence: 76%
“…The complementary specialisation of dogs' brain hemispheres is clearly apparent at different sensory levels, including vision [5], hearing [6][7][8][9][10] and what is considered to be the most relevant sensory domain for canine species, namely olfaction [11,12].…”
Section: Sensory Lateralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding voice-specific processing, we have solid data only for primates, but again, voice-selective regions exist, suggesting that such regions constitute a primate synapomorphy at least. One recent study on dogs suggests that the existence of voice-selective regions may extend more broadly among mammals (Andics et al 2014).…”
Section: Central Cortical Processing Of Vocalizationsmentioning
confidence: 99%
“…) Another option for neural studies is fMRI. This technique has recently been used to study voice-sensitive cortical regions in awake, unanesthetized dogs trained to lie still in an MRI scanner (Andics, Gácsi, Faragó, Kis, & Miklósi, 2014). Using the canine auditory fMRI method pioneered by Andics et al, one could determine if dogs, like humans, show increased activity in inferior frontal brain regions when hearing music that is harmonically complex versus simple, which would suggest cognitive processing of harmonic structure (cf.…”
mentioning
confidence: 99%